Sistem Cerdas Budidaya Jamur Tiram Berbasis Internet Of Things (IoT) - Eko Wahyu Santoso; Affan Bachri; Aura Arif Darmawan (Universitas Darul Ulum, 2025)
The cultivation of oyster mushrooms (Pleurotus ostreatus) requires optimal temperature and humidity control to ensure maximum growth. One of the main challenges faced by mushroom farmers is the difficulty in monitoring and controlling environmental conditions in real time, which can negatively impact yield quality and productivity. This study aims to design and implement an intelligent system based on the Internet of Things (IoT) to automatically monitor and regulate temperature and humidity in oyster mushroom cultivation rooms. The system utilizes an ESP32 microcontroller as the main controller, a DHT11 sensor for temperature and humidity measurement, a relay module as an automatic switch, a mist maker to maintain humidity, and a DC fan to control air circulation. Environmental data are transmitted in real time to a Telegram Bot application, allowing users to monitor conditions remotely via smartphones. The experimental results show that all system components functioned properly and responsively. The DHT11 sensor accurately detected temperature and humidity variations, the relay operated stably in controlling connected devices, the mist maker effectively increased humidity, and the DC fan successfully reduced room temperature. In addition, the Telegram Bot provided automatic notifications and responded to user commands without noticeable delay. Overall, the IoT-based intelligent system proved effective in maintaining stable environmental conditions for oyster mushroom cultivation, improving monitoring efficiency, and supporting farmers in enhancing both yield quality and productivity.